Technopreneur versus entrepreneur orientation in fashion design education / Rahayu Purnama, Rosita Mohd Tajuddin and Shaliza Mohd. Shariff - Purnama, Rahayu; Mohd Tajuddin, Rosita; Mohd. Shariff, Shaliza (Universiti Teknologi MARA, 2023)
The fashion industry requires technopreneurs, people who engage in technology-oriented entrepreneurship, to develop fashion designs that align with Industrial Revolution (IR) 5.0 and resolve technological and digitalisation-based complexities arising from this era. Entrepreneurship dimensions involve autonomy, innovativeness, risk-taking, proactiveness, and technology proficiency prove inadequate for technopreneurship following their constraint resources and access to and insufficient knowledge of foreign technopreneurship within fashion design. Thus, the research aimed was to identify and review technopreneur orientation literature from empirical domains: (i) entrepreneurial dimensions and (ii) entrepreneur-oriented technology or “technopreneurship” catalysts in fashion design. A systematic method entailing 25 pertinent articles from published Scopus-indexed journals between 2009 and 2021 was adopted. The paucity of research on the technopreneur dimension led to 10 dominant and representative articles extracted from Scopus-indexed journals and other relevant journals indexed by Google Scholar between 2002 and 2021. Notably, the current study recommended a conceptual technopreneur orientation framework in fashion design education. The content analysis of the past research revealed that technopreneur concept is crucial and must be engaged in designing a competitive fashion design education. The integration between entrepreneurial orientation and technopreneur concept will lead towards a competent graduate who will have an enhanced technology know-how with entrepreneur capabilities that will complement the needs of IR 5.0.